Outer surface lipoproteins of Borrelia burgdorferi activate vascular endothelium in vitro. - Sellati, T J (1996)
Previously, we reported that activation of vascular endothelium by the Lyme disease pathogen Borrelia burgdorferi results in enhanced expression of endothelial cell adhesion molecules and promotion of the transendothelial migration of neutrophils in vitro. To investigate the role of spirochetal lipoproteins in this process, we assessed the ability of a synthetic lipohexapeptide corresponding to the N terminus of B. burgdorferi outer surface protein A (OspA) to activate human umbilical vein endothelial cells (HUVEC). Using a whole-cell enzyme-linked immunosorbent assay, we demonstrated that OspA lipopeptide activated endothelium in a dose-dependent fashion, as measured by upregulation of E-selectin. Near-maximal stimulation was achieved with 100 micromolar lipopeptide. In addition, the lipopeptide increased expression of vascular cell adhesion molecule 1 (VCAM-1) and intercellular adhesion molecule 1 (ICAM-1). Similar results were obtained with 25 nM native OspA or lipidated recombinant OspA or OspB. Incubation of HUVEC with nonlipidated OspA peptide, nonlipidated recombinant OspA or OspB, or tripalmitoyl-S-glyceryl-cysteine had little or no effect on expression of these adhesion molecules. A mutant strain of B. burgdorferi that lacked OspA and OspB upregulated expression of E-selectin to the same degree as its wild-type counterpart, indicating that other spirochetal components also possess the ability to activate endothelium. Conditioned medium from HUVEC incubated with OspA lipopeptide or lipidated recombinant OspA induced chemotaxis of neutrophils in Boyden chamber assays, whereas the OspA preparations alone were devoid of chemotactic activity. When HUVEC grown on connective tissue substrates were treated with OspA lipopeptide, subsequently added neutrophils migrated across the endothelial monolayers. These results implicate the outer surface lipoproteins of B. burgdorferi as potential effector molecules in the promotion of a host inflammatory response.